Volleyball Skills Techniques and the Impact on Motor Fitness - Siva, M. (Journal of Neonatal Surgery, 2025)
The purpose of the study was to find out the Volleyball Skills Techniques and the Impact on Motor Fitness Volleyball is a widely played team sport known for its high-energy movements and strategic game play. This study provides an overview of volleyball's fundamental skills and techniques, focusing on serving, passing, setting, spiking, blocking, and digging, which are essential for player performance. The study also explores the sport’s impact on physical fitness, highlighting improvements in strength, endurance, agility, and flexibility. Additionally, the psychological benefits, such as enhanced mental resilience and teamwork, are examined. Two literature reviews from recent studies support the argument that volleyball improves both physical and mental attributes in players. The study concludes with recommendations for incorporating volleyball into school curriculums, promoting it as a lifelong sport, and developing training programs that target both physical and mental skills. The hypothesis suggests that regular volleyball participation will result in significant improvements in fitness levels and psychological well-being. Given its wide-ranging benefits, volleyball is recommended as an effective tool for promoting both physical fitness and social interaction.